Self-leadership [ how to become a more successful, efficient, and effective leader from the inside out - Bryant, Andrew; Kazan, Ana Lucia (McGraw-Hill, 2013)
It is generally accepted in the business literature that the heart of leadership is leading self. I believe that leading self is also the path to being a 'responsible' leader. This book tells you what to do if you want to get better at leading self